Dampak Teknologi Digital terhadap Kesadaran Bela Negara Mahasiswa Universitas Pembangunan Nasional “Veteran” Jawa Timur - Intan Nikmatul Fitri; Renita Enjel Siahaan; Moh. Zahri Valent Affandi; Muchamad Akbar (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study explores the impact of digital technology on state defense awareness among students of Universitas Pembangunan Nasional “Veteran” East Java. Through a quantitative survey involving 29 respondents, it was found that 62.1% of respondents consider state defense awareness very important, and 86.2% agree that digital technology makes it easier to access information related to state defense. However, 10.3% of respondents felt that technology has no significant effect on state defense awareness. These findings show that while digital technology has the potential to increase state defense awareness, challenges such as disinformation and low interest in state defense content still exist. This research recommends improving digital literacy and engaging campaigns to raise awareness among university students.